Industrial innovation, networks, and economic development : informal information sharing in low-technology clusters in India - Kamath, Anant (Routledge studies in development economics, 2015)
"This book offers an innovative examination of how 'low-technology' industries operate. Based on extensive fieldwork in India, the book fuses economic and sociological perspectives on information sharing by means of informal interaction in a low-technology cluster in a developing country. In doing so, the book sheds new light on settings where economic relations arise as emergent properties of social relations. This book examines industrial innovation and microeconomic network behaviour among producers and clusters, perceiving knowledge diffusion to be a socially-spatial, as much as a geographically spatial, phenomenon. This is achieved by employing two methods - simulation modelling, and (quantitative, qualitative, and historical) social network analysis. The simulation model, based on its findings, motivates two empirical studies - one descriptive case and one network study - of low-tech rural and semi-urban traditional technology clusters in Kerala state in southern India. These cases demonstrate two contrasting stories of how social cohesion either supports or thwarts informal information sharing and learning. This book pushes towards an economic-sociology approach to understanding knowledge diffusion and technological learning, which perceives innovation and learning as being more social processes than the mainstream view perceives them to be. In doing so, it makes a significant contribution to the literature on defensive innovation and the role of networks in technological innovation and knowledge diffusion, as well as to policy studies of Indian small firm and traditional technology clusters"--